2019
DOI: 10.15421/021919
|View full text |Cite
|
Sign up to set email alerts
|

Bifidogenic properties of cell-free extracts derived from probiotic strains of Bifidobacterium bifidum and Lactobacillus reuteri

Abstract: Comprehensive study of the biological activity of structural components and metabolites of “beneficial” microorganisms opens the prospects of efficient and rational use of their biotechnological potential in the correction of microecological and related disorders. The study tested proliferative activity and biofilm formation by Bifidobacterium bifidum probiotic strain under the influence of cell-free extracts containing structural components and metabolites of the probiotic strains of B. bifidum and Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
1
0
2
Order By: Relevance
“…The development of therapeutic agents based on bacterial derivatives for the correction of microecological disorders and the correct approaches to their use in clinical practice should be based on understanding of the mechanism of their action. In our previous study we have shown that cell-free extracts containing structural components and metabolites of probiotic B. bifidum and L. reuteri strains have a significant bifidogenic effect (Knysh, 2019). The present work was focused on studying the effect of cell-free extracts of probiotic origin on the basic physiological functions of opportunistic gram-negative microorganisms involved in the pathogenesis of dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…The development of therapeutic agents based on bacterial derivatives for the correction of microecological disorders and the correct approaches to their use in clinical practice should be based on understanding of the mechanism of their action. In our previous study we have shown that cell-free extracts containing structural components and metabolites of probiotic B. bifidum and L. reuteri strains have a significant bifidogenic effect (Knysh, 2019). The present work was focused on studying the effect of cell-free extracts of probiotic origin on the basic physiological functions of opportunistic gram-negative microorganisms involved in the pathogenesis of dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Застосування біологічно активних дериватів у складі безклітинних пробіотичних продуктів покликане вирішити проблему небажаних ефектів і недостатньої ефективності клітинних пробіотиків [4,15]. Нашими попередніми дослідженнями встановлено, що безклітинні екстракти, отримані шляхом дезінтеграції пробіотичних бактерій термоциклюванням з наступним культивуванням у власних дезінтегратах, здатні стимулювати проліферацію і біоплівкоутворення пробіотичних бактерій та пригнічувати ріст потенційних патогенів [7,8,9].…”
Section: вступunclassified
“…Для налагодження промислового виробництва постбіотичних засобів необхідними є науково і економічно обґрунтований спосіб отримання пробіотичних похідних та достатня доказова база їх біологічної активності, лікувальної ефективності та безпеки. Нами були розроблені оригінальні способи одержання дериватів пробіотичних штамів Bifidobacterium bifidum 1 і Lactobacillus reuteri DSM 17938 та в експериментах in vitro отримані дані, що демонструють високу інгібіторну щодо патобіонтів, стимуляторну щодо пробіотичних бактерій та імуномодуляторну активність дериват-вмісних безклітинних екстрактів (БКЕ) [12,13,14,15]. Зважаючи на те, що активність in vitro не можна ототожнювати з активністю in vivo, перед нами постало завдання дослідити ефективність застосування БКЕ при інфекційному процесі та дисбіозі у лабораторних тварин.…”
unclassified